Impact of market shocks on the wheat industry: an examination of supply chain responsiveness - Thomas, Raymond Joseph (Kansas State University, 2020)
Supply chain responsiveness is a topic that has been discussed by researchers and practitioners in business and economics. Many agribusiness firms attempt to understand responsiveness in a way that might help to respond to demand along the supply chain while experiencing uncertainty in consumer preferences and growing conditions. This study uses two classes of wheat to examine how the supply chain responded to a ‘shock’ in 2008. As prices changed, the use of grains in the U.S. and international markets changed as well. Firms that can respond to changes in the demand for their products are able to capitalize on market opportunities. The purpose of this research is to examine how supply chain responsiveness in the wheat industry is affected by a market shock. This study uses cycle-time as a proxy for supply chain responsiveness. A difference-in-difference regression analysis was used to estimate the before and after-effects of the 2008 wheat price increase, which is commonly associated with ethanol produced from corn and the time it took to respond to the new demand. The results indicated that a significant difference in planted acres and off-farm stocks had a negative relationship with responsiveness, while exports have and positive relationship. The time effect of Soft Red Winter Wheat, as the treatment group, did not display any significance. This would suggest that responsiveness after 2008 was not directly caused by the shock.
Keywords: Supply Chain Responsiveness; Market Shocks; Wheat